Brazilian legal changes in favor of children, adolescents and youth, and current issues (TEL Tempo, Espaço e Linguagem, 2026)
This article provides a retrospective of the social and rights situation of children, adolescents, and young people in Brazil from colonization to the implementation of the Estatuto da Criança e do Adolescente (Statute of the Child and Adolescent), highlighting the structural inequalities left behind and the changes generated. It emphasizes the need to guarantee the continuity of these achievements considering the current imposition of the conservative movements, using the practical implementation of the Estatuto da Juventude (Youth Statute) as a tool to combat those point of views, in order to apply the individual rights of children, but mainly to promote autonomy and non-blaming, including regarding women's sexual and reproductive rights, and to fight the punitive logics of peripheral populations, especially males, in order to definitively elevate them to the condition of subjects of rights.